KOMUNIKASI DI MEDIA SOSIAL - Anis, Aswhar (Penerbit CV Tentrem Karya Nusa, 2018)
Human life as a zoon politicon certainly can not be separated from the interaction with others, through what is called communication. The form of communication made by humans consists of various forms, ranging from intrapersonal communication, group communication, organizational communication, and mass communication. Through these forms of communication fellow human beings will exchange messages or information from the usual things to things that they consider important. Use of media facilities communication means today has grown so rapidly in line with advances in communication technology, where we are faced with many choice to be able to access, deliver/disseminate information both through conventional media such as print media and electronic media and the most developed is a new medium of online media (in the network) or often referred to as social media. The development of social media today has reached the easiest and fastest point in conveying and disseminating messages and information, one is ableto do it anytime and anywhere without being limited to space and time. Ease of communication is what then affects the social changes and behavior of individuals and communities.Key Word: Communication, Social Media, Community